Works for children and young adults : biographies - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Collected works of Langston Hughes, 2001)
The twelfth volume of The Collected Works of Langston Hughes contains Hughes's collections of biographies for children and young adults - Famous American Negroes, Famous Negro Music Makers, and Famous Negro Heroes of America - gathered together for the first time. In these works, Hughes sought to remedy decades of historical and cultural neglect by telling the stories of African Americans who had made vital contributions to the construction of the American identity. Hughes made clear his commitment to an inclusive and diverse accounting of the achievements of African Americans on American soil, from vernacular expression to high culture, oratory to combat, geographical exploration to intellectual introspection. His lively and dramatic portraits of African Americans such as Crispus Attucks, Frederick Douglass, Jackie Robinson, and Mahalia Jackson, battling against exclusivity and adversity to achieve their full potential, present a captivating portrait of America. This volume is a valuable record of the emerging African American struggle for civil rights and positive self- determination. It also documents Hughes's interests as he entered the fifth decade of his life and can be read fruitfully alongside his writings for adults at the time, reflecting his sociocultural and political thought.